The Effect of Inquiry-Based Learning Management Method (7E) along with Wordwall Games for Health Education Subject, Focusing on Classifying the 5 Main Food Groups for Third-Grade Students with Intellectual Disabilities - Kaewjaijong, Jarassree; Boonputtikorn, Chayarat; Khotmanee, Wittarit (RMUTK Journal of Liberal Arts, 2024)
This research aimed to study the learning achievement of students who have undergone inquiry-based learning (7E) combined with Wordwall games. The sample used in this research consisted of one third-grade student with intellectual disabilities (with an IQ ranging from 50-70) selected purposively from Suphanburi Panyanukul School, Suphanburi Province, in the academic year 2023. The research instruments included the learning management plan, Wordwall game, and achievement test. The statistics used in the research were mean ( ) standard deviation (S.D.) and percentage. The result revealed that students who received inquiry-based learning (7E) combined with the Wordwall game demonstrated improved after post-learning achievement according to the established criteria 80 percent.